Analisis Rasio Profitabilitas Dan Likuiditas Untuk Menilai Kinerja Keuangan Pada Pt. Kimia Farma Tbk - Muharram, Muhammad Yusuf; Ferawati, Yunda Dinar; Rakhmawati, Yunitsa; Putra, Angga Sanita (Peneliti.net, 2025)
Understanding and evaluating PT. Kimia Farma Tbk's financial performance in meeting its short-term obligations and its capacity to attain optimal performance in both areas of the studied ratio are the goals of the 2022–2023 liquidity and profitability ratio analysis. This study uses a descriptive method with a quantitative approach. The type and source of data used are secondary data obtained from the official website of PT Kimia Farma, Tbk. The study's findings, which are determined by the liquidity ratio, indicate that the company's 2023 volatility has left it in poor shape. Meanwhile, in the profitability ratio as a whole, the company's financial performance describes better results than in 2023 because the values of GPM, NPM, ROI and ROE have increased from the previous year.